A retrospective evaluation of acne patients treated with isotretinoin - Aksu, Fusun Eser (International Journal of Research in Medical Sciences, 2016)
Background: Although systemic isotretinoin offers more effective alternatives for treatment, as the drug has several side-effects, physicians are hesitatant to recommend the drug. The aim of this research was to retrospectively evaluate the effectiveness, side-effects and validity of systemic isotretinoin treatment on patients with acne, to thereby present experimental data relevant to future usage by patients suffering from acne. Methods: Patients diagnosed with acne in the Dermatology Polyclinic of the Medical Faculty of KSU between January 2004 and September 2008 was identified from the polyclinic records. Patient data were retrieved from the archives and recorded in the pre-prepared format. A retrospective evaluation was made of the safety and effectiveness of isotretinoin treatment, and the clinical and laboratory test side-effects. Results: A total of 241 patients were prescribed systemic isotretinoin treatment and started treatment. Of these, 129 of these patients attended regular follow-up examinations and completed the treatment. Systemic isotretinoin was determined to be effective on acne during a treatment period of 23.47±4.5 weeks with a total average dose of 113.73±22.4 mg. There were no serious laboratory test or clinical effects of an intolerable level tolerated which would lead to termination of the treatment. Conclusions: Systemic isotretinoin treatment is effective and safe for acne vulgaris patients with nodulocystic and papulopustular types of lesion. However, it is essential that the laboratory parameters of hepatic function tests and the lipid profile are checked regularly.